A label-free electrochemical immunosensor based on Au-BSN-rGO for highly-sensitive detection of β-amyloid 1–42. Issue 8 (3rd February 2023) - Li, Mengjiao; Yu, Qingjie; Zheng, Meie; Jiang, Rongrong; Zhu, Hongda; Guo, Huiling; Sun, Hongmei; Liu, Mingxing
Abstract : In this study, a label-free electrochemical immunosensor with high sensitivity for the detection of Aβ 1–42 was constructed based on Au-BSN-rGO. It has the advantages of low detection limits, high sensitivity and a wide linear range. Abstract : A label-free electrochemical immunosensor for high-sensitive detection of β-amyloid 1–42 (Aβ 1–42) was constructed based on Au-modified B, S, and N co-doped reduced graphene oxide (Au-BSN-rGO). The electronic structure of Au-BSN-rGO was investigated by first-principles calculations, which showed that the band gap of graphene was opened, thus improving its electrical conductivity. Moreover, Au-BSN-rGO was successfully prepared and characterized, and the obtained results discovered that it could be used as a signal amplifier for immunosensors due to the advantages of the good electrochemical characteristics and enormous surface area of BSN-rGO and the accelerated electron transfer ability of Au NPs. Furthermore, the label-free electrochemical immunosensor had a linear detection range of 0.1 pg mL −1 –10 ng mL −1 and a detection limit of 0.072 pg mL −1, and it had good specificity, stability, and reproducibility. Also, this immunosensor showed recoveries of 89%–109% with an RSD of 2.61%–4.19% for detecting Aβ 1–42 in actual sample analysis. Therefore, the label-free electrochemical immunosensor based on Au-BSN-rGO should have a promising clinical application prospect for detecting Aβ 1–42.